2014
DOI: 10.3354/ab00557
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the South American sea lion Otaria flavescens during the summer season at Río Negro, Patagonia, Argentina

Abstract: The South American sea lion Otaria flavescens population from northern Patagonia was under intensive commercial harvesting pressure between 1930 and 1950 and is currently increasing at a rate of nearly 6% yr −1. Food availability in the oceans is one of the most important factors influencing the survival and dynamics of marine mammal populations. The objective of the present study was to determine the summer diet of O. flavescens by faecal analysis, in order to assess its trophic behavior, determine whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
1
10
0
2
Order By: Relevance
“…In order to understand the ecological role of this otarid species in the local marine food webs, several dietary studies have already been performed using traditional methods (scats and stomach content analysis) or measuring the stable isotopic values from different tissues (e.g. bones, muscle, vibrissae) of SSL (George-Nascimento et al ., 1985; Thompson et al ., 1998; Naya et al ., 2000; Koen Alonso et al ., 2000; Drago et al ., 2009, 2010; Bustos et al ., 2012, 2014). These studies have indicated that fish, cephalopods and, to a lesser extent, crustaceans, constitute their most important prey.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the ecological role of this otarid species in the local marine food webs, several dietary studies have already been performed using traditional methods (scats and stomach content analysis) or measuring the stable isotopic values from different tissues (e.g. bones, muscle, vibrissae) of SSL (George-Nascimento et al ., 1985; Thompson et al ., 1998; Naya et al ., 2000; Koen Alonso et al ., 2000; Drago et al ., 2009, 2010; Bustos et al ., 2012, 2014). These studies have indicated that fish, cephalopods and, to a lesser extent, crustaceans, constitute their most important prey.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods are usually employed to identify dietary items such as stable isotopes, or recognition of structures like bones and otoliths (Boecklen, Yarnes, Cook, & James ; Jansen et al., ; Volpedo & Echeverría, ). To analyze feeding habits in marine mammals, birds and fishes the study of stomach contents provides information for recently ingested prey (Bustos, Daneri, Volpedo, Harrington, & Varela , ; Pierce & Boyle, ).…”
Section: Introductionmentioning
confidence: 99%
“…These inert structures record life history stage transitions of fishes (Brothers & McFarland, 1981) and may have a substantial importance when working in trophic studies and paleoecology. Identifying otolith morphology and morphometry found in fossils or in diet remains can determine not only species but also specimen size (Barrett et al, 2007;Bustos et al, 2012Bustos et al, , 2014Reichenbacher, Sienknecht, Küchenhoff, & Fenske 2007;Riet-Sapriza et al, 2013;Scartascini & Volpedo, 2013;Tuset, Parisi-Baradad, & Lombarte 2013;Tuset et al, 2015;Veen, Mullié, & Veen 2012). Even though otolith erosion, caused by digestion, is expected to decrease its length, otolith features are still a good approximation for trophic studies on species that are difficult to collect (Harvey, Loughlin, Perez, & Oxman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Usualmente se utilizan diferentes métodos para identificarítems dietarios como el análisis de isótopos estables o el reconocimiento de estructuras como huesos u otolitos, entre otros Boecklen et al, 2011;Jansen et al, 2012). Estas metodologías se aplican en el estudio del comportamiento alimenticio de mamíferos marinos, aves y peces, proporcionando información sobre las presas recientemente ingeridas (Pierce y Boyle, 1991;Bustos et al, 2012;Bustos et al, 2014).…”
Section: Introductionunclassified
“…Como se mencionó en el capítulo anterior, los otolitos son estructuras cuya morfología es especieespecífica (Hecht, 1987;Volpedo y Echeverría, 2001;Campana, 2004;Tuset et al, 2008;Avigliano et al, 2015a), por lo que se consideran estructuras valiosas para analizar cadenas tróficas en diferentes ecosistemas acuáticos tanto en el pasado como en la actualidad. La identificación de la morfología y morfometría de otolitos fósiles o en contenidos estomacales puede determinar no solo la especie, sino también el tamaño de las presas (Barrett et al, 2007;Reichenbacher et al, 2007;Bustos et al, 2012;Veen et al, 2012;Riet-Sapriza et al, 2013;Scartascini y Volpedo, 2013;Tuset et al, 2013;Bustos et al, 2014;Tuset et al, 2015).…”
Section: Introductionunclassified